Kedudukan Mahkamah Konstitusi dalam Proses Perubahan Konstitusi : Suatu Pendekatan Perbandingan antara Indonesia dan Chili - Arie Elcaputera (University Of Bengkulu Law Journal, 2024)
Constitutional amendment is a necessity to maintain the relevance of a country's basic law, but the process requires a monitoring mechanism to remain in accordance with democratic principles. The role of the Constitutional Court (MK) as the guardian of the constitution is crucial in ensuring that amendments do not deviate from the basic principles of the state. This research aims to comparatively analyse the role of the Constitutional Court in the constitutional amendment process in Indonesia and Chile from the perspective of constitutional law, as well as assess the relevance of Chile's constitutional experience for Indonesia. The research method used is normative juridical with a statutory approach and comparative law. The results of the study show that in Indonesia, the Constitutional Court does not have the authority to examine changes to the 1945 Constitution so that constitutional amendments are entirely the domain of the People's Consultative Assembly (formalistic approach). In contrast, in Chile, the Constitutional Court plays an active role in overseeing constitutional change with the authority to assess the suitability of amendments to fundamental principles (substantive approach), accompanied by a referendum mechanism to ensure popular participation. This comparison confirms that the involvement of the Constitutional Court in the amendment process can strengthen the principle of checks and balances and safeguard democratic values. In conclusion, the Chilean experience is relevant for Indonesia to consider in strengthening its constitutional system, for example through the adoption of a substance testing mechanism for amendments, a referendum, or an unamendable constitutional clause, in order to ensure a more democratic, transparent, and in line with the interests of the people.